2022
DOI: 10.3390/jcm11175078
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillometric Pulse Wave Analysis Is Useful in Evaluating the Arterial Stiffness of Obese Children with Relevant Cardiometabolic Risks

Abstract: Early detection of all complications of childhood obesity is imperative in order to minimize effects. Obesity causes vascular disruptions, including early increased arterial stiffness and high blood pressure. This study’s aim is to assess the reliability of pulse wave analysis (PWA) in obese children and how additional risk factors influence the evaluated parameters. We analyzed 55 children aged 6–18 years old by measuring their pulse wave velocity (PWV), augmentation index (AIx), peripheral blood pressure (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Arterial stiffness is influenced by numerous risk factors and biological processes. Arterial stiffness begins in early childhood, progresses in adulthood, and reflects the cumulative effects of cardiovascular risk factors on the vascular wall [ 14 , 15 ]. The occurrence and progression of arterial stiffness are closely linked to lipid and glucose metabolism, as well as to insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness is influenced by numerous risk factors and biological processes. Arterial stiffness begins in early childhood, progresses in adulthood, and reflects the cumulative effects of cardiovascular risk factors on the vascular wall [ 14 , 15 ]. The occurrence and progression of arterial stiffness are closely linked to lipid and glucose metabolism, as well as to insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the same study, they evaluated the PWV measured by tonometry and found no difference between the groups. Another recent study found a positive correlation between PWV and BMI in children [ 39 ]. Santos et al (2021) showed a positive correlation between PWV and BMI but an inverse correlation between AIx@75 and BMI; they concluded that BMI and anthropometric measurements would not be good predictors of arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Many years before, the successfulness of lifestyle changes was shown by Tuomilehto et al [ 36 ] who calculated that 22 subjects with PreD must be treated using non-pharmacological interventions in the primary care setting for one year (or five subjects for five years) to prevent one case of diabetes. Furthermore, obesity prevalence in children is growing worldwide and represents another crucial medical problem associated with increased arterial stiffness and BP values leading to accelerated atherosclerosis in early life [ 8 ]. Regardless of the age and CV risk, Zheng et al [ 14 ] showed (on 20,355 participants) that avoiding smoking, alcohol non-consumption, low salt intake and increased physical activity (ideal CV health) can reduce PWV and the risk of cardiac and cerebral events.…”
Section: Discussionmentioning
confidence: 99%
“…Micro- and macrovascular damage are associated with PreD and are presented by greater arterial stiffness and faster progression of atherosclerosis. The gold standard for determining arterial stiffness is pulse wave velocity (PWV) using tonometry or oscillometric devices; arterial stiffness is a known predictor of target organ damage (TOD), CVD and overall mortality [ 6 , 7 , 8 ]. An increase in PWV of 1 m/s compared to the reference value for age and sex is associated with a 14% higher cardiovascular (CV) risk [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%